1989
DOI: 10.1289/ehp.8982199
|View full text |Cite
|
Sign up to set email alerts
|

Use of longitudinal analysis of peripheral blood counts to validate historical reconstructions of benzene exposure.

Abstract: We studied over 17,000 peripheral blood counts, accumulated during hematologic surveillance from 1940 through 1975, from a cohort of 459 benzene-exposed workers. Linear regressions demonstrated significant decreases in white and red cell counts, as well as hemoglobin, for workers exposed during the 1940s, without persistent trends over the ensuing 25 years. Strongly positive correlations were observed between these blood count fluctuations and fluctuations in retrospective estimates of benzene exposures for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Many authors have shown that routine blood tests are not sensitive enough to detect early changes due to the toxic effects of benzene (17,28,31,(35)(36)(37)(38). According to the finding of this study, exposure to benzene concentrations below 1 ppm was reported in painters, causing few changes in blood cells, besides hematological changes associated with exposure to higher concentrations of benzene.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Many authors have shown that routine blood tests are not sensitive enough to detect early changes due to the toxic effects of benzene (17,28,31,(35)(36)(37)(38). According to the finding of this study, exposure to benzene concentrations below 1 ppm was reported in painters, causing few changes in blood cells, besides hematological changes associated with exposure to higher concentrations of benzene.…”
Section: Discussionmentioning
confidence: 58%
“…Exposure to high concentrations of benzene may decrease the blood cell count (30,31). Long-term exposure to different levels of benzene in the workplace may be associated with adverse health effects, such as reduced total WBC (32).…”
Section: Discussionmentioning
confidence: 99%
“…Benzene is widely used in the petroleum industry, and known a myelotoxic effect in human (Ert & Rhoads 1939, Thorpe 1974, Fishbeck et al 1978, Kipen et al 1989). Occupational exposure to benzene could decrease the levels of hemoglobin, white cell counts, absolute lymphocyte counts, and red cell counts, mean corpuscular volume, and platelets, as well as increase a risk of leukemia (Fishbeck et al 1978, Kipen et al 1989, Ward et al 1996, Khuder et al 1999, Duarte-Davidson et al 2001, Costantini et al 2003, Rothman et al 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational exposure to benzene could decrease the levels of hemoglobin, white cell counts, absolute lymphocyte counts, and red cell counts, mean corpuscular volume, and platelets, as well as increase a risk of leukemia (Fishbeck et al 1978, Kipen et al 1989, Ward et al 1996, Khuder et al 1999, Duarte-Davidson et al 2001, Costantini et al 2003, Rothman et al 1996. However, some studies suggested that benzene exposure could increase the red blood cell mean corpuscular volume (Fishbeck et al 1978, Rothman et al 1996.…”
Section: Introductionmentioning
confidence: 99%
“…This is manifested by decreased levels of antibodies and decreased levels of leukocytes in workers Cody, et al, 1993;Goldwater, 1941;Greenburg, et al, 1939;Kipen, et al, 1989;Lange, et al, 1973a,b;Ruiz, et al, 1994;Xia, et al, 1995;Yin, et al, 1987c). Animal data support these findings the peripheral blood and in bone marrow, leading to fibrosis, an irreversible replacement of bone marrow.…”
Section: Summary Of Health Effectsmentioning
confidence: 92%